Optimization of reaction parameters of esterification on the synthesis of palm oil-based alkyds using response surface methods - Beg, M. D. H.; Islam, M. R.; Ahmed, Badlishah; R. M., Yunus; Abdullah, Abu Hannifa (IOP Publishing, 2019)
In this research, polyalkyd resins were prepared from palm oil by polycondensation reaction. A two-step method viz., alcoholysis and esterification were conducted to synthesize polyalkyd resins. Response surface methodology was used to optimize the reaction parameters for esterification like reaction temperature, reaction time, catalyst concentration, acid anhydride to mono-glyceride ratio and agitation speed. The optimum condition was used to prepare various types of polyalkyds using different types of acid anhydrides such as, maleic anhydride, succinic anhydride, phthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride and cis-1,2-cyclohexanedicarboxylic anhydride. Result analyses through RSM revealed a desirability of 0.985 for the reaction time of 88.64 min. Moreover, 91.5% fractional conversion was achieved actually, which is close to the predicted value. The analysis revealed that 3,4,5,6-tetrahydophthalic anhydride-based resin showed improved resinous property than others due to the high degree of crosslinking.